A new taxon of Malgasian Liparis salassia (Orchidaceae, Malaxidinae) from Le RÈunion - Margońska, Hanna B.; Szelengowicz, Michel (Biodiversity: Research and Conservation, 2012)
A new variety of Liparis salassia (Pers.) Summerh. from Le Réunion Island is proposed and illustrated.